Pengaruh Cyberloafing Dan Leader Member Exchange Terhadap Innovative Work Behavior Melalui Kinerja Karyawan - Reza Andre Gunawan; Sutrisno Sutrisno; Heri Prabowo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research examines employees of Perum Jasa Tirta I Semarang. This research aims to determine the influence of cyberloafing and leader member exchange on innovative work behavior through employee performance. The research method in this research is a quantitative research method. The population in this study was all employees with a total of 10 employees who worked at Perum Jasa Tirta I Semarang, while the sample in this study was 180 respondents. Determining the sample size used a non-probability sampling technique because the population was relatively small, so the technique taken was saturated sampling (census). Data analysis in this research used the SmartPLS version 3 program. The data analysis technique used was the Structural Equation Modeling (SEM) equation model. The results of the analysis and discussion show that the perceived quality variable influences Cyberloafing, influences Innovative Work Behavior, Leader Member Exchange influences Innovative Work Behavior, Cyberloafing influences Employee Performance, Leader Member Exchange influences Employee Performance, Employee Performance influences Innovative Work Behavior, Cyberloafing influences on Innovative Work Behavior is partially mediated by Employee Performance, and Leader Member Exchange influences Innovative Work Behavior of Perum Jasa Tirta I Semarang employees which is partially mediated by Employee Performance.